The relationship between nurses’ professional commitment and patient safety with patients’ perceived care quality at Hospital Universiti Sains Malaysia - Al-Shlool, Sanaa Mohammad Khalaf (2021)
There is a need to enhance health care outcomes; particularly when nurses expend more time delivering clinical treatment for patients than other professionals do. Nurses thus have an important role in improving patient safety and quality of care. The primary objective of this study was to examine the relationship between nurses’ professional commitment, patient safety and patient-perceived care quality at Hospital USM, Malaysia. A descriptive, cross-sectional design was used to answer the research questions. Using the online survey method, 170 completed responses were collected from nurses. In addition, 170 questionnaires were collected completely from the patients with a response rate of 92% for both groups of respondents. Independent-sample t-test and one-way ANOVA were used to assess the relationship between sociodemographic data of nurses and patients with nurses’ professional commitment, patient safety and patient-perceived care quality. The result showed that the professional commitment level differs as the educational level of nurses altered. In addition, patient safety has a relationship with the specialty working area of nurses where the patient safety level was higher among nurses at obstetrics and gynecology wards. Moreover, the results revealed that patients at obstetrics and gynecology wards were satisfied more with nursing care quality than other patients who were admitted to the medical and surgical wards. Finally, the Pearson correlation results showed that nurses’ professional commitment has a positive relationship with patient-perceived care quality while no significant relationship with patient safety was found.